Hazelnut Has Potency on Wound Healing Associated with Immunohistochemical Biomarkers - Çirakli, Alper; Erdem, Havva (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: In this study, it was aimed to evaluate the impact of hazelnut on wound healing by using its immunohistochemical impacts on Claudin-5, Tumor Necrosis Factor-alpha (TNF-a), tumor Protein-63 (p63), and Insulin-like Growth Factor-1 (IGF-1) expression. Materials and Methods: Seventy-two male Wistar-Albino rats were used. Nine groups with 8 rats each group, and 3, 7, and 14 days groups were formed as oral, local, and control groups. Samples obtained from rats were evaluated with these immunohistochemical biomarkers. Results: Claudin-5 scores were found to be statistically significant in the oral group on all days (p=0.007, p=0.002, p=0,014). TNF-a scores were found to be statistically significant on the 3rd and 7th days in the local and oral groups (p=0.040, p=0.001). p63 scores were found to be statistically significant in the oral group when looking at the 14th day values (p=0.007). IGF-1 scores were found to be statistically significant on the 7th and 14th days in the local group (p=0.040). Conclusion: It was determined that hazelnut has positive impact on wound healing by stimulating the claudin-5, TNF-a, p63, and IGF-1expression levels.
Keywords: Wound; Healing; Hazelnut; Immunohistochemical; Biomarkers